Synthesis of Multi-substituted 4,5-Dihydrofuran Derivatives from (S)-Limonene and 1,3-Dicarbonyl Compounds and their Biological Activities - E. Findik; A. Dingil; I. Karaman; Y. Budak; M. Ceylan (E-Journal of Chemistry)
Multi-substituted 4,5-dihydrofuran derivatives were regioselectively synthesized by the reaction of α-carbo radical produced from 1,3-dicarbonyl compounds by oxidation with Mn(OAc)3 in Acetic acid and S-(-)-limonene. All the compounds were tested for their antibacterial and antifungal activities by the disc-diffusion technique.